Saving of Etalons in Image Processing Systems Based on the Parallel Shift Technology - Bilan, Stepan; Yuzhakov, Sergey; Bilan, Sergii (European Journal of Applied Sciences, 2015)
This article describes variants saving of etalons in image processing systems based on the parallel shift technology. The parallel shift technology can be used in hybrid image processing systems.